Sub-varieties of Malaysian English in Malaysian radio advertisements - Low, Sin Yen (2019)
The investigation of the language variety used in Malaysian radio advertisements is rarely a focus of research in Malaysia. Moreover, Malaysian English is not well-defined enough to be used as a depiction of Malaysian culture and identity. This paper aims to identify the lexical and syntactical structures of Malaysian English, and the frequencies of sub-varieties of Malaysian English (acrolect, mesolect and basilect) occur in Malaysian radio advertisements. Content analysis is carried out on the transcriptions of 80 Hitz FM radio advertisements collected from 30th August to 1st September 2018 to identify the lexical and syntactical features of Malaysian English in the radio advertisements. The openings, main-texts and closings of the radio advertisements are categorised according to the sub-varieties of Malaysian English. The frequencies of the occurrence of each sub-varieties of Malaysian English are recorded. The lexical and syntactical features of Malaysian English are found in the radio advertisements, but they are not prominent. The findings show that the acrolectal variety of Malaysian English dominates the structures of the radio advertisements, especially the closings. This may result from the preference of Malaysian listeners towards acrolectal variety of Malaysian English which carries professionalism, affinity and reliability. The dominance of the acrolectal variety in Malaysian radio advertisements shows that Malaysian English is not in the nativisation phase of Schneider’s Dynamic Model (2003). However, the use of lexical terms derived from local language referents is able to depict Malaysian culture and identity while still retaining the acrolectal variety of Malaysian English.